The New Age Worker: Morale and Strain Among Staff During a Correctional Staffing Crisis - Spanoudakis, Konstadina (Journal of contemporary criminal justice, 2024)
Correctional institutions have historically faced challenges in hiring and maintaining a workforce, which only increased during the COVID-19 pandemic. Considerable turnover in staff in recent years has led some states to lower the age of hiring eligibility, which in turn increases the number of new and younger officers on the job. This study explores the challenges and opportunities that the unprecedented change in the workforce in one Midwestern prison has had on workplace morale and strain. This study uses data from semi-structured interviews with a diverse group of correctional employees. We find a considerable disconnect between “new” and “old” correctional officers and offer policy solutions for future staffing practices.